Rectangular Array Model Supporting Students' Spatial Structuring in Learning Multiplication - Shanty, Nenden Octavarulia; Wijaya, Surya (Department of Doctoral Program on Mathematics Education, Sriwijaya University, 2012)
We examine how rectangular array model can support students' spatial structuring in learning multiplication. To begin, we define what we mean by spatial structuring as the mental operation of constructing an organization or form for an object or set of objects. For that reason, the eggs problem was chosen as the starting point in which the students could recognize such an arrangement. Geoboard was also be used as a tool to visualize the array. This research focused on a design research that was conducted in Surya Institute Program (SIP) in which investigated 12 Papuan students (between 10 and 11 years old) in connecting rectangular array model with the idea of multiplication. The result showed that rectangular array model indeed support the students to count things more efficient, able to see the structural similarities of arrays and created spatial structures for sets of objects.